First clinical experience with the Multi-LOC multiple stent delivery system for focal stenting in long femoro-popliteal lesions - Amendt, Klaus; Beschorner, Ulrich; Waliszewski, Matthias; Sigl, Martin; Langhoff, Ralf; Thalwitzer, Jörg; Redlich, Ulf; Heilmeier, Britta; Härtel, Dirk; Zeller, Thomas (Vasa, 2017)
Background: The purpose of this observational study is to report the six-month clinical outcomes with a new multiple stent delivery system in patients with femoro-popliteal lesions. Patients and methods: The LOCOMOTIVE study is an observational multicentre study with a primary endpoint target lesion revascularization (TLR) rate at six months. Femoro-popliteal lesions were prepared with uncoated and/or paclitaxel-coated peripheral balloon catheters. When flow limiting dissections, elastic recoil or recoil due to calcification required stenting, up to six short stents per delivery device, each 13 mm in length, were implanted. Sonographic follow-ups and clinical assessments were scheduled at six months. Results: For this first analysis, a total of 75 patients 72.9 ± 9.2 years of age were enrolled. The majority of the 176 individually treated lesions were in the superficial femoral artery (76.2 %, 134/176) whereas the rate of TASC C/D amounted to 51.1 % (90/176). The total lesion length was 14.5 ± 9.0 cm with reference vessel diameters of 5.6 ± 0.7 mm. Overall 47 ± 18 % of lesion lengths could be saved from stenting. At six months, the patency was 90.7 % (68/75) and all-cause TLR rates were 5.3 % (4/75) in the overall cohort. Conclusions: The first clinical experience at six months suggests that the MSDS strategy was safe and effective to treat femoro-popliteal lesions of considerable length (14.5 ± 9.0 cm). Almost half of the lesion length could be saved from stenting while patency was high and TLR rates were acceptably low.